"On Water" Surface‐initiated Polymerization of Hydrophobic Monomers. Issue 50 (14th November 2018) - Che, Yunjiao; Zhang, Tao; Du, Yunhao; Amin, Ihsan; Marschelke, Claudia; Jordan, Rainer
Abstract: We present the "on water" surface‐initiated Cu‐mediated controlled radical polymerization ("on water" SI‐CuCRP) that converts hydrophobic monomers in aqueous reaction medium to polymer brushes at unparalleled speed and efficiency. The method allows the facile conversion of a variety of common monomers under most simple reaction conditions and with minimal monomer amounts to thick and homogeneous polymer brushes. The highly living character of the "on water" SI‐CuCRP allowed the preparation of decablock (homo)polymer brushes and opens the pathway to sequentially controlled polymer brushes on solids. Abstract : (B)rush order : "On water" surface‐initiated Cu‐mediated controlled radical polymerization ("on water" SI‐CuCRP) is presented. By using this approach hydrophobic monomers in aqueous reaction medium and in the presence of oxygen are converted to polymer brushes at unparalleled speed and efficiency.